External evaluation and self-monitoring of the Baby-friendly Hospital Initiative's maternity hospitals in Brazil - Renara Guedes Araújo; Vânia de Matos Fonseca; Maria Inês Couto de Oliveira; Eloane Gonçalves Ramos (BMC, 2019)
Abstract Background In Brazil, the Baby-Friendly Hospital Initiative (BFHI) proposes following the criteria, the "Ten Steps to Successful Breastfeeding", International Code of Marketing of Breast-milk Substitutes and Good birth and delivery practices. Brazilian Baby-Friendly Hospitals are reassessed triennially by external evaluators and annually by self-monitoring. This study aimed to verify if the self-monitoring system fulfills its role of enabling accredited hospitals to assess and improve their compliance with the BFHI criteria. In this sense, we will analyze the self-monitoring evaluation results and compare them with those of the external reassessment. Methods This descriptive evaluation study of the compliance with the BFHI criteria by the Brazilian Baby-Friendly Hospitals by self-monitoring evaluators from 2010 to 2015 and by external evaluators in 2015. Results Self-monitoring was performed in all years from 2010 to 2015 by 143 BFHI accredited hospitals. The trend of the levels of compliance with BFHI's criteria according to self-monitoring evaluations was stable over the assessed period. Most criteria presented compliance above 70%, except Step 4 (skin-to-skin contact and breastfeeding in the first hour of life), with mean compliance of 67%. Steps 1 (written policy), 7 (rooming-in) and 9 (give no artificial teats) showed mean compliance above 90%. Regarding the external evaluation carried out in 2015, the criteria with lowest compliance were Step 4 and Woman-Friendly care, both below 50%. Steps 9 and 10 (refer mothers to breastfeeding support groups) reached levels of compliance above 90%. For 2015, self-monitoring provided significant higher compliance levels than those from external evaluations in most criteria, except Step 3 (prenatal information on breastfeeding) and Step 10. There was a difference of more than 30% points between evaluations of Steps 1 (written policy), 2 (training), 5 (show mothers how to breastfeed), Woman-Friendly Care and father or mother stay with their newborn. Conclusions The self-monitoring system fulfilled partially its role of allowing accredited hospitals to self-assess and improve rates of compliance with BFHI criteria. Future trainings of hospital managers need to address difficulties and identify solutions to improve implementation of Steps 4 and 6.